The performance of a passively Q-switched Cr:YAG4+ in an end- pumped laser system - Rasheed, Fareed F.; Jassim, Jassim M.; Jassim, Saad Y. (Iraqi Journal of Laser, 2009)
A characteristic study of a passively Q-switched diode pumped solid state laser system is presented in this work. For laser a comparison study for the theoretically calculated results with a simulation results using a software which calculates the Q-switched solid state laser parameters was such as energy, peak power and pulse width were performed. There was a good agreement between our theoretical calculations and the simulation values.